The role of experiential knowledge within attitudes towards genetic carrier screening: A comparison of people with and without experience of spinal muscular atrophy. (13th July 2017) - Boardman, Felicity K.; Young, Philip J.; Warren, Oliver; Griffiths, Frances E.
Abstract: Purpose: Autosomal recessive conditions, while individually rare, are a significant health burden with limited treatment options. Population carrier screening has been suggested as a means of tackling them. Little is known, however, about the attitudes of the general public towards such carrier screening and still less about the views of people living with candidate genetic diseases. Here, we focus on the role that such experience has on screening attitudes by comparing views towards screening of people with and without prior experience of the monogenetic disorder, Spinal Muscular Atrophy. Methods: An exploratory sequential mixed methods design was adopted. In‐depth qualitative interviews were used to develop two surveys. The surveys addressed attitudes towards carrier screening (pre‐conceptual and prenatal) for SMA. Participants: 337 participants with SMA experience completed the SMA Screening Survey (UK) and 336 participants with no prior experience of SMA completed the UK GenPop Survey, an amended version of the SMA Screening Survey (UK). Results: The majority of both cohorts were in favour of pre‐conception and prenatal carrier screening, however people with experience of type II SMA were least likely to support either. Key differences emerged around perceptions of SMA, with those without SMA experience taking a dimmer view of the condition than those with. Conclusion: This study underscores the significance of prior experience with the condition to screening attitudes. It highlights the need for accurate and high‐quality educational resources to support any future carrier screening programmes, that particularly in relation to rare genetic disorders like SMA that will fall outside the remit of everyday experience for the majority of the population.